Myocardial ischemia: narrative drug targets and management by ethnobotanicals - batool, Amna; hasan, Umme; abid, Farah; Utra, Ambreen; maqsood, Umer; Shaukat, Bushra (International Journal of Pharmacology and Toxicology, 2017)
Cardiac ischemia is characterized by imbalance between oxygen demand and its supply to myocardium owing to atherosclerotic plaques, which results in moderate to severe damage to heart function. Ischemic heart disease leads to cardiac arrhythmia and heart failure. Various therapeutic interventions, including lifestyle modification, pharmacological treatment options and surgical procedures are available. Besides these therapies, ischemic patients have to suffer from cardiac events repeatedly. Therefore, novel treatment modalities directed towards LDL cholesterol synthesis, oxidation of LDL, monocyte/macrophage recruitment, foam cells, platelet aggregation, cytokines and extracellular matrix comprising of smooth muscle cells have been found to be the promising targeted therapies. Moreover, drugs of ethnobotanical origin might be safer, effectual and economic, thus improving the quality of life.